Kinsey rapport : over vrouwelijke en mannelijke homoseksualiteit - Bell, Alan P.; Weinberg, Martin S.; Van Emde Boas, C.; Nijs, Paul; Kerkhoven, Hanneke (Amsterdam Brussel : Elsevier, 1979)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie